Rural Student Analysis : Correlation Science Process Skills and Critical Thinking at a State Senior High School in Jambi Province - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Wita Ardina Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Science process skills and critical thinking skills are skills and abilities that must be possessed by students. So the purpose of this study is to determine the science process skills and students' critical thinking skills in the physics learning process in terms of female gender and male gender. In addition, the purpose of this study is to see how the differences and the relationship between science process skills and students' critical thinking skills are. This type of research is quantitative research with an experimental research design. The population of this study itself is the students of SMAN 6 Batanghari with a total sample of 101 people from class XII IPA1, XII IPA 2 and XII IPA 3. The sample selection technique used is total sampling technique. The instruments used in this study were observation sheets and critical thinking test instruments and interest questionnaire. The data analysis technique used is descriptive statistics and inferential statistics, Correlation hypothesis testing. The results of this study are both science process skills and students' critical thinking skills are in the good category. However, the dominant gender is women who are in the good category with a percentage of 57.6% and men in the good category with a percentage of 51.9%. Meanwhile, for students' critical thinking skills, women were in a good category with a percentage of 59.8 and men in a good category with a percentage of 47.3. There are differences in science process skills and critical thinking skills between men and women. And there is a relationship of 0.357 between science process skills and students' critical thinking skills.